ANALISIS PERAN KANTOR URUSAN AGAMA (KUA) DALAM PENINGKATAN POTENSI WAKAF PADA MASYARAKAT DI KECAMATAN BAJENG KABUPATEN GOWA - Syamsani; Amin, Muhammadiyah; Mustarin, Basyirah (Universitas Islam Negeri Alauddin Makassar, 2025)
This research discusess the analysis of the role of KUA in increasing the potential of waqf in the communityin Bajeng district, Gowa Regency. The problems that will be studied are:1) what is the KUA’s stategy for increasing the potential of waqf in the community in Bajeng District, Gowa Regency? 2)what are the community in Bajeng District, Gowa Regency? This type of research is qualitative research, namely research with field data as the main data source. Data collection methods in this research are observation, interview and dokumentation. This research resulth show that 1)KUA Bajeng District, Gowa Regency is effective in increasing the potential of waqf through data collection,certification, socialization and implementation of the E-AIW application. This startegy also involves the role of religious figures and collaboration with the ministry of religion. As result, waqf management becomes more effective,transparent and beneficial to society. 2)KUA obstaclesin increasing the potential of waqf in the people ogf Bajeng District include internal obstaclessuch as limited fasilities, infrastructure and lack of understanting about waqf and economic conditions that are not yet optimal, this has an impact on the community’s lack of interest in waqf. The implications of this research include: developing the potential of waqf in Bajeng District, Gowa Regency requires a comrehensive strategy. Improving waqf socialization and education, managing and empowering waqf land, as well as legalizing waqf land is very important. Collaboration between the office of religious affairs, the ministry of religion and the community is also needed to optimize the potential of waqf and also so thet waqf in Bajeng District can be further developed and the hope is that it will not only be used as means of worship or educational facility, but can develop in a productive waqf that is beneficial to the community. As well as areference for the Bajeng District KUA in making future decisions regarding efforts to increase waqf in Bajeng District.Keywords: Waqf Potential, Religious Affairs Office, Public.